2022
DOI: 10.3389/fpsyt.2022.927817
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Plasma Lipids in Adult Women With Major Depressive Disorder and Bipolar Depression

Abstract: Lipidomics has been established as a potential tool for the investigation of mental diseases. However, the composition analysis and the comparison of the peripheral lipids regarding adult women with major depressive depression (MDD) or bipolar depression (BPD) has been poorly addressed. In the present study, age-matched female individuals with MDD (n = 28), BPD (n = 22) and healthy controls (HC, n = 25) were enrolled. Clinical symptoms were assessed and the plasma samples were analyzed by comprehensive lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…However, there are some classes of lipids that tend to display potential as biomarkers for BD throughout the literature ( Table 1 ). Four of the 9 reports that used omics methods found glycerophospholipids to be altered in BD ( 44 , 107 , 108 , 109 ), and 4 publications also reported altered levels of sphingolipids in BD ( 44 , 108 , 109 , 110 ). Four studies reported altered glycerolipids ( 44 , 108 , 109 , 110 ), and 3 reported altered levels of free fatty acids ( 91 , 108 , 111 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are some classes of lipids that tend to display potential as biomarkers for BD throughout the literature ( Table 1 ). Four of the 9 reports that used omics methods found glycerophospholipids to be altered in BD ( 44 , 107 , 108 , 109 ), and 4 publications also reported altered levels of sphingolipids in BD ( 44 , 108 , 109 , 110 ). Four studies reported altered glycerolipids ( 44 , 108 , 109 , 110 ), and 3 reported altered levels of free fatty acids ( 91 , 108 , 111 ).…”
Section: Resultsmentioning
confidence: 99%
“…, 2022 ( 111 ) Cholesterol, fatty acids GC-MS CC Serum Zhang et al. , 2022 ( 109 ) Glycerolipids, glycerophospholipids, sphingolipids LC-MS CC Plasma BP, bipolar disorder; CC, case-control; DE, depressive episode; FEP, first-episode psychosis; GC, gas chromatography; H-NMR, nuclear magnetic resonance; LC, liquid chromatography; MaE, manic episode; MiE, mixed episode; MS, mass spectrometry; PAF, platelet-activating factor; UHPLC, ultrahigh performance liquid chromatography. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four studies on MDD patients included more than one hundred individuals (Table S1). Six studies evaluated a broad panel of different lipid markers [34,[58][59][60][61][62]. Consensual data were received for LPC and LPE measurements, which were increased in the observed studies.…”
Section: Lipids and Their Role In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Transdiagnostic between SCZ, MDD, BPD, and AD: ↓ 10-nitro-9Z,12Z-octadecadienoic acid decreased; ↑ 9,12-octadecadienal, cyclopentaneoctanoic acid, hexadecandioic acid, 12-tridecynoic acid, and caprylic acid [79]. ↓ [61].…”
Section: Carnitinementioning
confidence: 99%